The Effect of Interactive Management Style on Academic Adjustment, Math Anxiety and Academic Engagement of Students - Ghasemzadeh Alishahi, Abolfazl; Panahi, Mojtaba; Samadi, Maryam (Iranian Journal of Educational Sociology, 2022)
Purpose: The purpose of this study was to examine the effect of interactional management style on academic adjustment, mathematical anxiety, and academic engagement in elementary sixth grade students.Methodology:  This research was applied in terms of purpose and quasi-experimental in terms of method and with pre-test-post-test design with experimental group and control group. The statistical population consisted of all male students of the elementary sixth grade of district 3 of Tabriz city with a total of 3721 students in the academic year of 2018-2019. The sample size was 57 persons (29 experimental and 28 control) and selected by purposive sampling method. Clark academic adjustment questionnaire, Shokrani mathematical anxiety questionnaire, and Schofley and Becker academic engagement questionnaires were used for data collection. The interactional management style was also implemented based on the researcher-designed package. Descriptive and inferential statistical methods including univariate and multivariate analysis of covariance were used for data analysis.Findings:  Results showed that after applying an interactive management style, the mean of academic adjustment in the experimental group was significantly higher than the control group. The mean of mathematical anxiety and its components (mathematical test anxiety and anxiety of mathematical nature) in the experimental group were significantly lower than the control group. The mean of academic engagement and its components (ability, commitment, and attraction) in the experimental group were significantly higher than the control group.Conclusion: The study concluded that teacher-student interaction improved academic engagement and academic adaptation and reduced student math anxiety.